Comparison of Her-2/Neu Gene Amplification or Expression between IHC and FISH in BC - Zhang, Qinqin; Jin, Lei; Gong, Hua (Cellular and Molecular Biology, 2022)
This study aimed to analyze and compare the application of FISH and IHC in BC tissue Her-2 / neu gene amplification or expression. For this purpose, 110 patients with BC were selected. FISH and IHC were performed on the BC tissues that were surgically removed, and the results were compared and analyzed. The results showed that in 110 BC tissues, the expression of HER-2 protein was (+++) 25 cases (22.73%); (++) 44 cases (40%); (+) 26 cases (23.64%); (1) 15 cases (13.64%). There were 42 cases of HER-2 gene amplification in 110 BC tissues, and 68 cases had no amplification. IHC test positive (+++) is consistent with FISH positive coincidence rate, IHC test negative (+/-) is consistent with FISH negative coincidence rate, IHC test suspicious positive (++) compared with the FISH result, the difference is statistically significant. However, the total coincidence rate between IHC test results and FISH test results was 89.29 (25/28), and the two test methods were positively correlated. Generally, IHC positive and negative expressions are in good agreement with FISH test results. The suspected positive expression of IHC is inconsistent with the FISH test result, suggesting that the IHC test is suspicious, and the positive specimens need to be tested by FISH.